Shocks and Social Protection : Lessons from the Central American Coffee Crisis, Volume 2, Detailed Country Cases - World Bank (Washington, DC, 2012)
A major objective of this report is to provide a deeper, more policy relevant understanding of the welfare impacts of the coffee crisis - including the effects of the crisis on household income, consumption, poverty, as well as on basic human development outcomes, such as education and child nutrition. To do this, the study has generated a body of new empirical evidence, drawing from an unusually rich collection of household survey data from El Salvador, Guatemala, Honduras, and Nicaragua. This includes "panels" of data from Nicaragua, El Salvador, and Honduras that enable one to track changes in welfare of the same households over the period of the crisis. This has helped to provide a more detailed, clearer understanding of the crisis than has been available to date. Given the prevalence of both natural and economic shocks in Central America, another key objective of the study is to draw out the broader policy lessons of the coffee crisis - to enhance the abilities of the region's governments to respond to a range of shocks in a timely and effective manner. To do this, the report draws not only on evidence specific to the coffee crisis, but to other recent analysis on the role and efficacy of different safety net programs in the face of different types of shocks. By learning the lessons of recent experience, Central American governments, along with their development partners, can be better prepared to deal with a variety of different shocks in the future. In pursuing its objectives, the report has been organized into two volumes. Volume I presents a synthesis of the key findings and policy implications, focusing both on the impacts of the coffee crisis, specifically, and the lessons for government responses to shocks, more generally. Volume 2 goes into more detail on the specific impacts of the coffee crisis, presenting the collection of background studies commissioned for this report.